2017
DOI: 10.3390/medicines4040085
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Danshen (Salvia Miltiorrhizae Radix et Rhizoma) and Sanqi (Notoginseng Radix et Rhizoma) Combination in Angiogenesis Behavior in EAhy 926 Cells

Abstract: Background: This study investigated the combination effects of the Danshen and Sanqi herb pair on angiogenesis in vitro. Methods: Nine combination ratios of Danshen-Sanqi extracts (DS-SQ) were screened for their angiogenic effects in the human vascular endothelial EAhy 926 cell line via cell proliferation, cell migration and tube formation activities against the damage to the cells exerted by DL-homocysteine (Hcy) and adenosine (Ado). The type of interaction (synergistic, antagonistic, additive) between Danshe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…25 It was also found that Salvia miltiorrhiza and P. notoginseng had synergistic effect and considerably promoted the growth and angiogenesis of human vascular endothelial EAhy 926 cells. 26 P. notoginseng belongs to the family of Rattan, which can be used clinically to maintain microcirculatory homeostasis and treat diseases such as diabetic dysfunction. 27 NR1 is a plant androgen isolated from Sanqi (also known as P. notoginseng (Burk.…”
Section: Discussionmentioning
confidence: 99%
“…25 It was also found that Salvia miltiorrhiza and P. notoginseng had synergistic effect and considerably promoted the growth and angiogenesis of human vascular endothelial EAhy 926 cells. 26 P. notoginseng belongs to the family of Rattan, which can be used clinically to maintain microcirculatory homeostasis and treat diseases such as diabetic dysfunction. 27 NR1 is a plant androgen isolated from Sanqi (also known as P. notoginseng (Burk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several mathematical models such as the combination index (CI) and isobologram method, both of which can differentiate between synergistic and additive effects, have been extensively used to quantify the true synergistic interaction in phytomedicines, ( Zhou et al, 2016b ). For instance, our previous study applied the CI and isobologram models to identify synergistic interaction in a commonly used pair of herbs, Salvia miltiorrhiza and Panax notoginseng , in reducing inflammation, endothelial apoptosis and promoting angiogenesis ( Zhou et al, 2016a ; Zhou et al, 2017 ; Zhou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Danshen-Sanqi herbal pair (DS-SQ) has been popular used as the Chinese herbal medicine for prevention and treatment of cardiovascular diseases, including stroke, myocardial infarction and angina pectoris [17]. Recently, DS-SQ was reported having a variety of biological and physiological effects such as protective effects on cell survival in the human cardiovascular endothelial [18], anti-inflammatory activity [19] and inhibition of retina cell apoptosis [20]. A study by Yue et al revealed that DS-SQ showed cardio-protective effects against ischemia-reperfusion injury [21].…”
Section: Introductionmentioning
confidence: 99%